In-vitro Comparison of Trifocal Intraocular Lenses of Different Optical Zone Diameter and Design Across Pupil Sizes - Łabuz, Grzegorz; Niknahad, Ava; Yan, Weijia; Son, Hyeck-Soo; Khoramnia, Ramin; Auffarth, Gerd U. (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Trifocal intraocular lenses (IOLs) for the correction of cataracts allow patients to enjoy good uncorrected intermediate and near visual acuity, and allow them to be independent of spectacles. While clinical studies robustly support their advantages, laboratory evaluations of their objective performance are important. This study evaluated novel trifocal IOLs with 6.0 or 7.0 mm optical zone – Triva-aAY or Triva-aXAY – and compares them to a classic trifocal (Acrysof IQ PanOptix) and an extended-depth-of-focus trifocal (Triumf POD L GF).Methods and Material The optical quality of two samples of each IOL model with a diopter power of 20 D was evaluated at 3-, 4.5-, and 6-mm apertures with OptiSpheric IOL PRO2 and measured per ISO 11 979 standard. The resulting modulation transfer functions (MTF), through focus area under the MTF curve (MTFa) and simulated visual acuity (VA) were assessed at near, intermediate, and far distances. Additionally, IOLʼs tolerance to misalignment was measured by inducing up to 0.7 mm of vertical decentration and 5° tilt. Measurements were repeated with the 1951 United States Air Force (USAF) resolution test chart.Results The Triva-aXAY and Triva-aAY had equivalent optical performance at all apertures. For the 3- and 4.5-mm pupil, the Triva IOLs showed MTF levels close to that of the PanOptix but had a slightly extended focus range at a near distance. The MTF analysis did not reveal any difference in optical quality between the Triva IOLs at 6 mm. Although at far and intermediate focus, the Triumfʼs MTF was above the level of the other models, it was at the expense of the near focus. Triumf was the least tolerant of misalignment. All findings were supported by the USAF resolution test charts.Conclusion Triva-aXAY and Triva-aAY IOLs have an equivalent optical performance at all apertures, with a slightly extended focus range compared to PanOptix at near focus, comparable MTF at intermediate focus, and lower optical quality than Triumf at far focus. The latter, however, may provide insufficient performance at reading distance. IOL misalignment affects the optical quality of the trifocal models and is design-dependent.
Keywords: cataract surgery; optical quality; modulation transfer function; trifocal intraocular lenses